Genes, genesis and God Radio interview with Rachael Kohn (Radio National - Australia) - Rolston, Holmes, 1932-2025, speaker; Kohn, Rachael, speaker; ABC Radio National, producer (Colorado State University. Libraries, 2003)
Science and religion are distinct, yet overlap. Biology finds "selfish genes" but also self-actualizing genes, defending their kind. Charles Birch, Australian biologist, celebrates life. Rolston's quarrels with both science and religion for not finding intrinsic value in nature. Rolston notoriously has advocated shooting rhino poachers and keeping cattle of the poor off tiger sanctuaries. One ought to fix a problem in the right place. Rolston recalls receiving the Templeton Prize in Buckingham Palace, then giving it the same day to his alma mater. He was millionaire for six hours.
Dr. Rolston speaks with Rachael Kohn on ABC Radio National about the religious and scientific values that have made his work, such as Genes, Genesis and God, and Environmental Ethics, among the most respected and quoted throughout the world.
Accessibility features: Transcript.
Keywords: religion; Rolston, Holmes, 1932-2025; Templeton Prize; philosophy professor; science; Colorado State University; environmental ethics